Contribution of the novel inflammatory bowel disease gene IL23R to disease susceptibility and phenotype. - Cummings, JR; Ahmad, T; Geremia, A; Beckly, J; Cooney, R; Hancock, L; Pathan, S; Guo, C; Cardon, L; Jewell, D (2007)
BACKGROUND: A North American genome-wide single nucleotide polymorphism (SNP) association study identified IL23R as a novel inflammatory bowel disease (IBD) susceptibility gene. Association was reported with multiple risk variants in the centromeric portion of IL23R in 3 large independent cohorts. The aims of this study were to replicate the association of IL23R with Crohn's disease (CD), examine subphenotype relationships, and look for evidence of epistasis with the known CD susceptibility gene CARD15 and susceptibility haplotype IBD5 in a large collection of CD patients. We further investigated the relationship between IL23R and ulcerative colitis (UC). METHODS: In all, 604 CD and 647 UC patients who had been rigorously phenotyped and who had been recruited from a single UK center were used in this study. Controls were either spouses of patients (141) or were recruited from well-person clinics (993). Eight SNPs were genotyped using MassArray (Sequenom). All 8 SNPs genotyped were significantly associated with CD. RESULTS: The association with the nonsynonymous SNP rs11209026 was confirmed (P=6.65x10(-6), odds ratio [OR], 0.43, 95% confidence interval [CI]: 0.29-0.64). The most significant SNP in our study was rs7517847 (P=4.9x10(-9), OR 0.65, 0.56-0.75), which is statistically independent of rs11209026. Preliminary evidence suggests an epistatic interaction with the IBD5 risk haplotype. The effects of mutations in this IL23R appear weaker in UC (P=0.008, OR 0.63, 0.45-0.89 and 0.005 OR, 0.81, 0.71-0.94, respectively). No subphenotype associations were identified. CONCLUSIONS: We confirmed the findings that IL23R is a susceptibility gene for IBD with suggestive epistasis with the IBD5 locus in the CD population.